2016
DOI: 10.3847/2041-8205/829/2/l32
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Atlas: Discovery of Patchy Clouds and High-Amplitude Rotational Modulations in a Young, Extremely Red L-Type Brown Dwarf

Abstract: Condensate clouds fundamentally impact the atmospheric structure and spectra of exoplanets and brown dwarfs but the connections between surface gravity, cloud structure, dust in the upper atmosphere, and the red colors of some brown dwarfs remain poorly understood. Rotational modulations enable the study of different clouds in the same atmosphere, thereby providing a method to isolate the effects of clouds. Here we present the discovery of high peak-to-peak amplitude (8%) rotational modulations in a low-gravit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
118
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(139 citation statements)
references
References 62 publications
17
118
3
Order By: Relevance
“…We performed the data reduction using the same method as in previous works published by our group (Apai et al 2013;Buenzli et al 2014;Yang et al 2015;Lew et al 2016). The uncertainty level for our spectra after the data reduction is 0.1%-0.3% per spectral bin, measured using the reduced spectra in the range of 1.1-1.69μm to avoid the noise at the edges of the spectra due to the drop in the instrument sensitivity.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the data reduction using the same method as in previous works published by our group (Apai et al 2013;Buenzli et al 2014;Yang et al 2015;Lew et al 2016). The uncertainty level for our spectra after the data reduction is 0.1%-0.3% per spectral bin, measured using the reduced spectra in the range of 1.1-1.69μm to avoid the noise at the edges of the spectra due to the drop in the instrument sensitivity.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…To date, published light curves of various ultracool dwarfs show single or double peaks, whose shapes vary with time, sometimes even within a single rotation (Artigau et al 2009;Radigan et al 2012;Apai et al 2013;Gillon et al 2013;Buenzli et al 2015;Karalidi et al 2015;Metchev et al 2015;Lew et al 2016;Yang et al 2016). These observations are interpreted as single or multiple cloud structures in the atmosphere of brown dwarfs that can evolve at short timescales.…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude of variability as a function of wavelength samples the vertical depths of cloud layers (Apai et al 2013), and amplitude spectra have been shown to vary with effective temperature (T ef f ; e.g., Yang et al 2015) and surface gravity (e.g., Lew et al 2016). Wavelength-dependent phase variations in lightcurves have also been observed (Buenzli et al 2012;Biller et al 2013;Yang et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Broad-band variability amplitudes are typically <1% in L and T dwarfs, with some dramatic exceptions (Artigau et al 2009;Radigan et al 2012;Gillon et al 2013;Lew et al 2016). Ground-based spectral (e.g., CLOUDS; Goldman et al 2008) and broad-band photometric monitoring surveys (e.g., Bailer-Jones & Mundt 1999;Koen 2003;Radigan et al 2014;Wilson et al 2014) are generally limited to >1-3% relative precision due to telluric atmospheric instabilities (i.e., "red noise") and insufficient numbers of nearby reference stars which can be used to correct time-variable telluric absorption (Bailer-Jones & Lamm 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, most recent time-resolved spectroscopic studies are limited to low spectral resolution with a resolving power of ∼100. These observations imposed limits on particle sizes in BD atmospheres (Lew et al 2016) and mapped surface spots and faculae coverage (Burgasser et al 2014;Karalidi et al 2016).…”
Section: Introductionmentioning
confidence: 99%